PUBLIC-PRIVATE PARTNERSHIP AS A MECHANISM OF INNOVATIVE ECONOMIC DEVELOPMENT - Zhadan O. V. (Pressing Problems of Public Administration, 2021)
The article is devoted to the development of theoretical and methodological provisions and methodological recommendations based on world experience on the formation of mechanisms of public-private partnership in the innovation sphere of Ukraine’s economy. The essential characteristics of public-private partnership in the innovation sphere, principles and organizational forms of its functioning are specified. The comparative analysis of the processes of public-private partnership development in Ukraine and the leading countries of the world is carried out. Several of the most significant problems that hinder the development of PPP in Ukraine have been identified: imperfection of the legislative and regulatory framework; fiscal orientation of tax legislation; lack of long-term financing mechanisms; low level of business confidence in government; lack of a clear concept of PPP development and support; shortcomings of the judicial system; high levels of corruption and various kinds of abuse and arbitrariness, which is a major obstacle to the development of private funding not only in the regions but also at the level of national projects; the influence of the political component on economic decision-making. The priority directions of the state policy on further improvement of mechanisms of public-private partnership in the innovation sphere are formulated: creation of the favorable economic and normative-legal environment based on effective interaction of the state, business, science and society; development of new organizational mechanisms of the public-private partnership system; creation of a system of state support for the results of innovation activities; formation of entrepreneurs motivation for the development of innovative activities; development of new organizational mechanisms of the public-private partnership system; introduction of effective tools of state management of the innovation sphere; providing state guarantees for business loans to introduce knowledge-intensive technologies; elimination of imbalance between the interests of the state and private business; stimulating organizational and institutional support for entrepreneurship; involvement of small and medium business in participation in targeted programs and innovative projects; development of antitrust measures to develop competition in knowledge-intensive industries. Thus, currently the trend of formation and development of public-private partnerships is an objective basis for effective interaction of economic entities of the business sector and government, ensuring the consolidation of material and financial resources, as well as a more even distribution of commercial and financial risks between them.